Estudo genealógico das viagens, dos viajantes e dos turistas - FIGUEIREDO, Silvio José de Lima (2012)
This article presents a genealogical study of traveling and tourism – important concepts for the understanding of western societies – through the analysis of a number of writings, some of them representing a milestone in literature, history, and anthropology. We examine the construction of ideas of traveling, tourism, traveler, and tourist, based on literature and in reports of two “agents” that were important both for the formation, and for the crystallization of such notions. We realize that ideas on traveling and tourism found in literature and in reports are reproduced in cultural post-modern products, transforming actions, characters, and personalities into stereotypes.